Controllable crystal form transformation and luminescence properties of up-conversion luminescent material K3Sc0.5Lu0.5F6: Er3+, Yb3+ with cryolite structure. Issue 48 (8th September 2021) - Yan, Zhaoliang; Guo, Qingfeng; Liao, Libing; Shuai, Pengfei; Huang, Feifei; Mei, Lefu
Abstract : Controllable crystal form transformation can effectively influence the up-conversion luminous intensity of cryolite materials. Abstract : In this paper, a novel cryolite-type up-conversion luminescent material K3 Sc0.5 Lu0.5 F6 : Er 3+, Yb 3+ with controllable crystal form was synthesized by a high temperature solid state method. K3 Sc0.5 Lu0.5 F6 : Er 3+, Yb 3+ can crystallize in monoclinic or cubic form at different temperatures. The composition, structure and up-conversion luminescence (UCL) properties of K3 Sc0.5 Lu0.5 F6 : Er 3+, Yb 3+ samples with different crystal form were investigated in detail. It is impressive that both monoclinic and cubic forms of K3 Sc0.5 Lu0.5 F6 : Er 3+, Yb 3+ show green emission ( 2 H11/2 / 4 S3/2 → 4 I15/2 ). The luminescence intensity of cubic K3 Sc0.5 Lu0.5 F6 is much higher than that of the monoclinic form, and the reasons are also discussed in detail. The results show that the luminescence intensity of up-conversion materials can be effectively tuned by controlling the crystal form. According to the power dependent UCL intensity, the UCL mechanism and electronic transition process were discussed. In addition, the fluorescence decay curves were characterized and the thermal coupling levels (TCLs) of Er 3+ ( 2 H11/2 / 4 S3/2 → 4 I15/2 ) in the range of 304–574 k were used to study the optical temperature sensing characteristics. All the results show that K3 Sc0.5 Lu0.5 F6 : Er 3+, Yb 3+ can be used in electronic components and have potential application value in temperature sensing fields.